IMPLEMENTASI DISPENSASI PERKAWINAN PASCA DIKELUARKAN REVISI UNDANG-UNDANG PERKAWINAN - Vily Easter; Mia Hadiati (Jurnal Hukum Adigama, 2022)
A legal marriage is a marriage that is carried out between a man and a woman and the marriage islegally registered according to the law in force in Indonesia. If a man and a woman have not reachedthe minimum age for marriage and wish to marry, they can apply for a marriage dispensation at theReligious Courts or at the District Courts according to the religion of both parties. Examples includethe application for dispensation from marriage in the Sumedang Religious Court Decision Number541/Pdt.P/2020/PA.Smdg and the Sumedang Religious Court Decision Number475/Pdt.P/2020/PA.Smdg. The problems that occur in the research of this thesis, namely what is thebackground of the filing of a marriage dispensation, how is the judge's consideration in deciding theapplication for a marriage dispensation, and how is the ef ectiveness of Law No. 16 of 2019 onapplications for a marriage dispensation. This thesis research uses a normative research method wherethe approach used is a conceptual approach, a legal approach, a case approach supported by data andliterature reviews and also interview data to strengthen the research material of this thesis. After 1(one) month the issuance of the latest revision of the Marriage Law, BADILAG noted that applicationsfor dispensation for marriage experienced a fairly rapid increase from the previous year, this was dueto a change in the minimum age limit for marriage which changed to 19 years for both men andwomen. woman. Then the judge's consideration in deciding the application is to see the benefit of thePetitioner's child, on that basis the judge grants the marriage dispensation application and issupported by the completeness of the requirements for submitting a marriage dispensation application.Unfortunately, the latest Marriage Law is considered less ef ective in suppressing the rampantmarriage of minors which continues to this day.